2021
DOI: 10.1007/s00268-021-05979-8
|View full text |Cite
|
Sign up to set email alerts
|

Strong for Surgery: Association Between Bundled Risk Factors and Outcomes After Major Elective Surgery in the VA Population

Abstract: Background Strong for Surgery (S4S) is a public health campaign focused on optimizing patient health prior to surgery by identifying evidence‐based modifiable risk factors. The potential impact of S4S bundled risk factors on outcomes after major surgery has not been previously studied. This study tested the hypothesis that a higher number of S4S risk factors is associated with an escalating risk of complications and mortality after major elective surgery in the VA population. Methods The Veterans Affairs Surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this issue of World Journal of Surgery, Liou and colleagues in their novel analysis ''Strong for Surgery: Association Between Bundled Risk Factors and Outcomes After Major Elective Surgery in the VA Population'' evaluate the impact of modifiable risk factors on perioperative outcomes [5]. Through the Veterans Affairs Surgical Quality Improvement Project (VASQIP) database, Liou et al identified 31,285 patients who underwent major elective procedures between 2008 and 2015 in the Veterans Affairs system with preoperative nutrition laboratories, hemoglobin A1c, and smoking status recorded.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of World Journal of Surgery, Liou and colleagues in their novel analysis ''Strong for Surgery: Association Between Bundled Risk Factors and Outcomes After Major Elective Surgery in the VA Population'' evaluate the impact of modifiable risk factors on perioperative outcomes [5]. Through the Veterans Affairs Surgical Quality Improvement Project (VASQIP) database, Liou et al identified 31,285 patients who underwent major elective procedures between 2008 and 2015 in the Veterans Affairs system with preoperative nutrition laboratories, hemoglobin A1c, and smoking status recorded.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients‐adjusted mortality risk increased in a stepwise fashion as they added on risk factors: one risk factor (aOR, 1.34) and two risk factors (aOR, 1.58). Furthermore, this trend held true for postoperative complications as well: The strongest predictor of postoperative complications was the presence of all three risk factors (aOR, 5.20) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications in the perioperative period are increasingly being attributed to comorbidities and other patient risk factors (e.g., smoking, suboptimal nutritional status) 1‐3 . Studies have shown that these risk factors in surgical patients have been linked to increased lengths of stay; more emergency department visits; greater need for reoperation; higher rates of readmission, transfusion, and surgical site infections; and increased mortality 2,3 . The timeframe before surgery, when patients may be particularly open to positive behavioral messages, can provide a unique opportunity to address these risk factors 4 .…”
mentioning
confidence: 99%